2018
DOI: 10.1111/efp.12484
|View full text |Cite
|
Sign up to set email alerts
|

A versatile method for assessing pathogenicity of Hymenoscyphus fraxineus to ash foliage

Abstract: We describe a method for inoculating rachises of Fraxinus excelsior (European or common ash) with Hymenoscyphus fraxineus, which is faster than previous methods and allows associated foliar symptoms to be assessed on replicate leaves. A total of ten ash seedlings were inoculated with five isolates of H. fraxineus and lesion development assessed over four weeks. A five‐point disease progress scale of symptom development was developed from no l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
9
1
Order By: Relevance
“…We found no correlation between growth of the fungus in vitro and disease progress in the stem in our study. This can at first sight seem in contrast to the finding of Orton et al (), who discovered a strong correlation between in vitro growth and the length of rachis lesions. However, the disagreement between the two studies could be due to the inoculation of different tissue types (leaves vs. stem).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…We found no correlation between growth of the fungus in vitro and disease progress in the stem in our study. This can at first sight seem in contrast to the finding of Orton et al (), who discovered a strong correlation between in vitro growth and the length of rachis lesions. However, the disagreement between the two studies could be due to the inoculation of different tissue types (leaves vs. stem).…”
Section: Discussioncontrasting
confidence: 96%
“…However, the disagreement between the two studies could be due to the inoculation of different tissue types (leaves vs. stem). Orton et al () suggested that in vitro growth can serve as a precise proxy for growth in leaves; this would indicate that isolates in our study, such as Hf 22.1, that cause no stem necroses but grow fast in vitro may indeed be competitive when spreading in leaves. Difference in growth in rachis and stem could be due to either physiological differences or differences in the genetic control of resistance between tissue types.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Insect frass has emerged as a non-invasive DNA source for multiple types of genetic studies, including those of beetles. This has included studies of pathogen infection of both beetles and their host plants [38] and dietary analysis [39]. Frass has also been utilized for molecular species identification, which can be indispensable in distinguishing closely related species [30].…”
Section: Discussionmentioning
confidence: 99%
“…The spread of ash dieback disease across the United Kingdom follows a pattern largely consistent with the distribution of ascospores of Hymenoscyphus fraxineus from the east (Timmermann et al ., ). However, there have been few attempts to follow infection from ascospore inocula (Cleary et al ., ; Fones et al ., ; Mansfield et al ., ; Orton et al ., ). The symptoms of the disease, involving death and browning of leaves and stems, suggest that the pathogen has a distinctive necrotrophic mode of infection (Gross et al ., ; Stenlid et al ., ).…”
Section: Introductionmentioning
confidence: 98%